Evaluation of Civics Learning in Building Character of Elementary School Students: A Study in the Context of the Independent Curriculum - Ningsih, Citra Yulia; Daffa, Falih; Ariga, Selamat (Yayasan Zia Salsabila, 2023)
This study aims to evaluate the effectiveness of artificial intelligence (AI)-based learning media in improving students' understanding, reasoning, and communication in Citizenship Education (PKn) learning in Elementary Schools or Madrasah Ibtidaiyah, in the context of the Merdeka Curriculum. The main problem faced is how the use of this technology can support the development of students' character and strengthen understanding of citizenship values. The research method used is a qualitative approach with a case study at MI Asy-Syafi'iyah Kendari. Data were collected through observation, interviews with teachers and students, and documentation analysis. The data analysis technique used the NVivo application to identify patterns and themes that emerged from qualitative data. The results of the study showed that AI-based media were effective in improving understanding of PKn teaching materials, as well as helping students develop verbal and nonverbal communication skills. Another significant impact is the improvement in the quality, creativity, and collaborative attitudes of students. This study confirms that the integration of technology in learning can strengthen students' character and deepen citizenship literacy, but also identifies challenges related to teacher skills and equal access to technology. Recommendations for this study include the importance of teacher training and increasing access to technology across regions.